The Ecovillage of Pescomaggiore (L'Aquila): Birth and death of a self-determined post-disaster community (2009-2014). Issue 4 (5th August 2019) - Tomassi, Isabella; Forino, Giuseppe
Abstract : Purpose: The purpose of this paper is to aim at exploring the relationship between community building and the changes occurred in the context of a post-disaster self-built ecovillage ( EcoVillaggio Autocostruito (EVA)), spontaneously born after the L'Aquila earthquake in 2009. The community eventually dissolved in 2014, following a series of changes in the organization, that resulted in an increasingly centralized decision-making process, and in individual and community relationships, that were fueled by conflicts and contrasts. Design/methodology/approach: Through a self-ethnography method, the paper provides the insider perspective of the lead author who was a part of EVA since the beginning. Self-ethnography allowed developing a narrative of EVA across its life course. Findings: Findings reveal that the community into EVA was initially pursuing community-building goals through self-construction, sustainability, mutuality and reciprocity relationships out of market. However, several events occurred and changed community goals, organization and decision making. Eventually, individual goals and vertical decision making emerged among the community members, leading to the death of EVA. Research limitations/implications: The paper just considered those main events that marked the collective and individual life of the lead author since the beginning until the end of the ecovillage. Others events, equally important, were not considered due to word length. In addition, self-ethnography is still considered by some authors as a subjective method. Originality/value: The paper is one of the few exploring community experiences into post-disaster ecovillages. Moreover, there are no papers investigating post-disaster ecovillages through a self-ethnography approach. Therefore, the paper offers an innovative and original perspective on the under-investigated topic of post-disaster ecovillages and employs a promising research method in disaster studies.